TEACHER’S COPING STYLE STRATEGY WITH MISBEHAVING STUDENTS - Ningsih N.L.K.D.; Putra I N.A.; Ramendra D.P. (Lingua Scientia, 2019)
The study aimed at: a) finding out kinds of students’ misbehavior and b) describing the English teachers’ strategies in handling students’ misbehavior.The participants of this research were four English teachers who taught in Grade 5 at DS, a bilingual school in Denpasar, in school year 2017/2018. This study was a descriptive qualitative study. There were three instruments used to collect the data namely observation sheet, interview guide and questionnaire. The data were analyzed by using interactive data analysis model including four steps namely data collection, data reduction, data display and drawing conclusion and verification. The findings revealed that: a) there were 10 different kinds of students misbehaviors at school namely inattention, needless talk, moving about the room, annoying others, disruption, lying, stealing, sexual harassment, aggression and fighting and also defiance of authority; b) The teachers used 6 different coping styles strategies in handling misbehaving students such as hinting, reward and recognition, punishment, aggression, social problem solving and relaxation. The results of this study were expected to be beneficial in giving additional knowledge for the English teachers of primary school in managing their classroom especially in a context of bilingual school system.